Strength characteristics of cement stabilized construction waste slurry modified by polyacrylamide with different moisture contents - Guo, Feng; Hu, Jiabin (Frontiers in Materials, 2024)
Waste slurry is a major component of construction waste, and its resource utilization can effectively reduce its environmental impact. The effect of polyacrylamide (PAM) content and moisture content on the strength characteristics of PAM modified cement stabilized construction waste slurry (PCMS) was studied using unconfined compressive strength (UCS) and triaxial tests.It can be concluded that, 1) The UCS of PCMS increases with the increase of curing age and significantly decreases with the increase of moisture content. As the content of PAM increases, it first increases and then decreases, with UCS reaching its maximum at a PAM content of 0.5%. 2) When the moisture content is 50%, PAM can increase the elastic modulus of PCMS. When the content of PAM is 0.5%, the elastic modulus reaches its maximum value. When the moisture content is 80% and 100%, the effect of PAM on the elastic modulus of PCMS is not significant. 3)The addition of PAM can improve the shear strength of PCMS. Under the same confining pressure, the shear strength of PCMS increases first and then decreases with the increase of PAM content, and the optimal content is 0.5%. 4) The variation pattern of PCMS cohesion is basically consistent with the shear strength. PAM improves the shear strength of PCMS by enhancing its cohesion. The addition of PAM has a relatively small impact on the internal friction angle of PCMS. These findings provide valuable insights for research into modification technology and the resource utilization of construction waste slurry.